Pemberdayaan Generasi Muda untuk Pendidikan Cemerlang dan Pembangunan Berkelanjutan di Yayasan An-Nahl Alfarizqi Barkah - Syahidah, Hilyah; Finzalia, Dinda; Ginawati, Emi; Fadhillah, Muhamad Arya; Syta, Putri Nabilla (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
The problem of lack of access to education and quality of education for children at the An-Nahl Alfarizqi Barkah Foundation, Desa Leuweung Kolot, is a significant challenge. This is influenced by parents' low level of education and a less supportive environment. Community service activities through the Sustainable Management Capstone program with a direct instructional method, which is carried out through discussion and practice, aim to build strong, disciplined, and adaptive characters to create an environment that supports sustainable character education. Learning is focused on seven main programs, namely Environment, English, Outbound, Agriculture, Mathematics, and Pancasila and Citizenship Education which are guided by field supervisors. Overall, the results of community service activities through the Sustainable Management Capstone program have added to the provision of skills and values ​​that are relevant to the education of children at the An-Nahl Alfarizqi Barkah Foundation.